MEKANISASI USAHATANI PADI DI KECAMATAN SANANWETAN KOTA BLITAR - cristina Ratnawati (Universitas Merdeka Madiun, 2020)
Mechanization is one form of technology adoption to improve yields in rice farming. The aims of the research to determine the use of agricultural mechanization and its impact on rice farming in Sananwetan Sub-District, Blitar City expected to improve the standard of living and welfare of its group members. The number of samples taken was 50 rice farmers in Sananwetan Sub-District, Blitar City, chosen by using proportional random sampling. Data analysis using the Mann-Whitney Test and the Multiple Linear Regression Cobb Douglas Model. From the results of interviews in this study show that the use of the mechanization of rice farming in Sananwetan Sub-District, Blitar City is still not optimal. This was due to farmers' perceptions of the unsatisfactory results of agricultural machinery performance, a sense of humanity to 'farm laborers', narrow land area and insufficient availability of farm machinery. While from the results of Mann Whitney's test show that pesticide use and labor requirements were smaller and differed significantly in the use of full mechanization rather than partial mechanization. Other than that, the variable cost of the harvest is lower in the use of full mechanization and is significantly different compared to using the mechanism partially. Rice productivity in full mechanization was 782.15 kg / 1000m2 while partial mechanization was 682.87 kg / 1000m2. For farmers' income in full mechanization is IDR. 1,153,407, - per 1000 m2, in the partial mechanization of IDR. 1,590,574, - per 1000m2. From Cobb Douglas model multiple linear regression analysis found that land area (m2), seed costs and the use of mechanization had a significant effect on the income of rice farming in Sananwetan District, Blitar City.